Exploring the novel environmentally friendly highly hydrophobic TiO2 coating for enhanced anti-corrosion performance of steel in potential industrial applications - Haewon Byeon; J. Sunil (Results in Chemistry)
In this study, the structural and morphological properties and the corrosion resistance of mild steel (MS) plates were enhanced through the development of titanium dioxide (TiO2) nanoparticles applied using the doctor blade coating method. X-ray diffraction (XRD) analysis, Rietveld refinement, and Fourier-transform infrared spectroscopy (FTIR) confirmed the successful synthesis of TiO2 nanoparticles. The TiO2 nanoparticles were bound to hydroxyl and carboxyl functional groups through electrostatic interactions. Field emission scanning electron microscopy (FESEM) images revealed the nanoparticles' minor agglomeration and spherical morphology. Additionally, particle size analysis showed a distribution range between 45 and 50 nm, with an average size of 48.56 nm. Surface wettability analysis demonstrated enhanced aqueous repellence of the MS plates after TiO2 coating, particularly in NaCl, HCl, and KOH electrolytes. In addition, the TiO2 nanoparticle coatings exhibited optimized nano-hardness values of 2.79 GPa, 1.51 GPa, and 2.89 GPa after electrochemical analysis, indicating an increase compared to the values measured before the electrochemical studies. The TiO2-coated MS samples exhibited significantly improved corrosion resistance compared to bare MS samples under 1 M H2SO4, 3 M KOH, and 3.5 wt% NaCl electrolytes. Potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) results revealed that the TiO2 coating achieved the lowest corrosion current density (1.7839 μA/cm2) and the highest protection efficiency (80.24 %) in NaCl electrolyte. Furthermore, EIS analysis indicated that the TiO2 coating effectively impeded electrolyte penetration to the substrate, thereby providing superior corrosion resistance.